2015
DOI: 10.1016/j.neulet.2014.10.051
|View full text |Cite
|
Sign up to set email alerts
|

High aggression in rats is associated with elevated stress, anxiety-like behavior, and altered catecholamine content in the brain

Abstract: The social defeat paradigm involves aggressive encounters between Long-Evans (LE) (resident) and Sprague-Dawley (SD) (intruder) rats. Successful application of chronic social defeat stress in SD rats is dependent upon selection of highly aggressive LE rats. Half of the LE rats screened for aggression did not meet the criterion for aggression (LE rats performing a defeat, characterized by the intruder surrendering or acquiring a supine position for at least 3 sec). The observation of the differences in the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Significantly decreased concentration of DA and increased concentration of NA were observed in the brain in many pathophysiological conditions. For example, significantly decreased concentration of DA and increased concentration of NA were observed in the prefrontal cortex in aggressive rats [21]. Also, the decreased concentration of DA was observed in many psychiatric and neurological disorders.…”
Section: Discussionmentioning
confidence: 96%
“…Significantly decreased concentration of DA and increased concentration of NA were observed in the brain in many pathophysiological conditions. For example, significantly decreased concentration of DA and increased concentration of NA were observed in the prefrontal cortex in aggressive rats [21]. Also, the decreased concentration of DA was observed in many psychiatric and neurological disorders.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, Clozapine mainly works by improving the tonic stimulation of D1-receptors in the PFC (Ahlenius, 1999), which may normalize D1-to-D2 receptor activation and thereby improve cognitive stability and control of immediate tendencies in primary psychopathy. Similarly, preliminary results in rats showed that high levels of impulsive aggressiveness is associated with lower PFC DA levels (Patki et al, 2015), suggesting that increasing PFC DA levels may improve control of aggressive tendencies. In other words, when given to severely disinhibited psychopaths, Clozapine may bias their mesocortical DA profile towards a more controlled psychopathic profile.…”
Section: Summary and Future Directionsmentioning
confidence: 86%
“…In rodent models, high aggressive individuals exhibit greater anxiety-like behaviors and possess elevated NE and EP concentrations in the prefrontal cortex and amygdala as well as elevated EP in the hippocampus [33]. However, after D2 antagonism in laying hens, birds exhibited reduced aggression and tended to reduce feather pecking.…”
Section: Anxiety-related Behaviorsmentioning
confidence: 99%
“…Anxiety-related behaviors, including fearful and damaging behaviors have been linked to both aggression and catecholaminergic systems [33]. In rodent models, high aggressive individuals exhibit greater anxiety-like behaviors and possess elevated NE and EP concentrations in the prefrontal cortex and amygdala as well as elevated EP in the hippocampus [33].…”
Section: Anxiety-related Behaviorsmentioning
confidence: 99%